Transverse Skin Crease versus Vertical Midline Incision versus Laparoscopy for Right Hemicolectomy: A Systematic Review—Current Status of Right Hemicolectomy. (30th January 2014) - Santoro, Alberto; Boselli, Carlo; Renzi, Claudio; Gubbiotti, Francesca; Grassi, Veronica; Di Rocco, Giorgio; Cirocchi, Roberto; Redler, Adriano
Abstract : Purpose . The right hemicolectomy may be conducted through laparoscopic or laparotomic surgery, transverse or midline incisions. The transverse laparotomy offers some advantages compared to the midline laparotomy and laparoscopy. A literature review was performed to evaluate the possible advantages of the transverse incision versus midline incision or laparoscopic right hemicolectomy. Methods . A systematic research was performed in Medline, Embase, Cochrane Central Register of Controlled Trials, CINAHL, BioMed Central, and the Science Citation Index. Results . Laparotomic right hemicolectomy with transverse incision is preferable to laparotomic hemicolectomy with midline incision. A transverse incision offers a lessened postoperative pain following physical activity, a lessened need to administer analgesic therapy during the post-operative time, better aesthetic results, and a better post-operative pulmonary function. Open surgery with transverse or midline incision ensured a shorter operative time, lower costs and a greater length of the incision compared to the laparoscopic. However, there are no differences in the oncological outcomes. Conclusions . It was not possible to identify significant differences between the open right hemicolectomy with transverse incision versus the open right hemicolectomy with midline incision or laparoscopic hemicolectomy.